Off-Label Immunosuppressant Drugs in Solid Organ Transplantation - Rita Nogueiras-Álvarez; María del Mar García-Sáiz (MDPI AG, 2024)
Once a solid organ transplantation (SOT) has been performed, it is necessary to prescribe immunosuppressant medication to prevent graft rejection. This task has the peculiarity that many of these drugs do not have specific indications for transplant use in the technical data sheets. We performed a review of different immunosuppressive drugs' information available at European and American regulatory agencies in order to analyze the approved indications by the type of SOT. In our work, besides showing these differences between different indication approvals in different SOT modalities, we also attempted to reflect other differences under the approved indications according to age group, formulation type, geographical area, etc. Although consensus documents on the subject have been published, the access to immunosuppressants depends on each country's regulation and healthcare system, and off-label prescription is a reality that healthcare professionals need to be familiar with.